Feasibility of early functional rehabilitation in acute stroke survivors using the Balance-Bed—a technology that emulates microgravity - Oddsson, Lars I. E.; Finkelstein, Marsha J.; Meissner, Sarah (Frontiers in Systems Neuroscience, 2015)
Evidence-based guidelines recommend early functional rehabilitation of stroke patients when risk of patient harm can be managed. Current tools do not allow balance training under load conditions sufficiently low for acute stroke patients. This single-arm pilot study tested feasibility and safety for acute stroke survivors to use “Balance-Bed”, a technology for balance exercises in supine initially developed to emulate microgravity effects on balance. Nine acute stroke patients (50-79 yrs.) participated in 3-10 sessions over 16-46 days as part of their rehabilitation in a hospital inpatient setting. Standard inpatient measures of outcome were monitored where lack of progress from admission to discharge might indicate possible harm. Total FIM scores at admission (median 40, range 22-53) changed to (74, 50-96), Motor FIM scores from (23, 13-32) to (50, 32-68) and Berg Balance scores from (3, 0-6) to (19, 7-43) at discharge. Changes reached Minimal Clinical Important Difference for a sufficient proportion (>0.6) of the patients to indicate no harm to the patients. In addition, therapists reported the technology was safe, provided a positive experience for the patient and fit within the rehabilitation program. They reported the device should be easier to set up and exit. We conclude acute stroke patients tolerated Balance-Bed exercises such as standing on one or two legs, squats, stepping in place as well as balance perturbations provided by the therapist. We believe this is the first time it has been demonstrated that acute stroke patients can safely perform whole body balance training including balance perturbations as part of their rehabilitation program. Future studies should include a control group and compare outcomes from best practices to interventions using the Balance-Bed. In addition, the technology is relevant for countermeasure development for spaceflight and as a test-bed of balance function under microgravity-like conditions.